Selecting habitat to what purpose? The advantage of exploring the habitat-fitness relationship - Uboni, Alessia; Smith, Douglas W.; Stahler, Daniel R.; Vucetich, John A. (Ecosphere, 2017)
Measures of reproductive success have been recognized in many fields as essential tools to assess the status of populations, species, and communities. However, difficulties in gathering data on reproductive success often prevent researchers from taking advantage of the information offered by those measures. For example, most of habitat selection studies do not include reproductive success in their analysis even though doing so would highly improve our understanding of the habitat selection process. In our study, we aimed to assess to what extent habitat selection choices made by adult individuals are directed to increase their annual reproductive success. We tested this idea by first developing habitat selection models and then relating the results of those models to two measures of reproductive success. Using wolves, Canis lupus, as the study species, we determined that not all habitat selection choices performed by adult wolves were related to their annual reproductive success. The results varied also in relation to the measure of reproductive success used in the analysis and other individual-, group-, and population-level factors. Likely, adult female wolves select habitat characteristics to increase not only their annual reproductive success but also their lifetime reproductive success, for example, by ensuring their own survival and reproductive abilities in subsequent years. Our study suggests that a variety of motivations may govern habitat choices performed by adult individuals and including different measures of fitness in habitat selection studies can improve our understanding of these complex processes.